Chapter Remote working in Italy: Just a pandemic accident or a lesson for the future? - Bollani, Luigi (Proceedings e report, 2023)
During the Covid-19 pandemic, remote working (RW) has been a way to producing despite limiting contacts. In Italy, about a half of the workers experienced, at least for a part of their working time, RW during the years 2020 and 2021. In this paper we analyse the data collected through a web-based survey conducted in the second half of 2021 at a convenience sample of Italian adults. The survey was aimed at highlighting how Italians experienced the pandemic and how they perceived their future. Also, we measured the frequency and the intensity of the RW phenomenon, the feelings of those who practiced and the opinion of workers about the possibility to practice it in the future. The data show that so many adults practiced RW during the pandemic. Their judgement of the experience is largely positive: 60.8% stated they were inclined to pursue it again as a normal work strategy. Though, there are distinctions. The type of job and the recent experience entail people's commitment towards RW. Even what people expect from work may influence their disposition to take in RW as normal. The convolution of wells of the RW disposition, scouted through a multivariate statistical analysis, showed that, on top of the well-known suitability of RW to certain job types (white-collar, gig activities, self-employed), the workers' propensity to RW is higher if commuting cost saving, own time optimisation and not-too-open schedules, work-family balance and a free time surplus, the possibility of interaction and socialisation with other company's employees and customers and a secure web connection characterise their jobs.